A Sermon for the Ceremony of the Funeral of Stephen the First, of Blessed Memory, the Most Glorious King of Poland, by Martinus Laterna of the Society of Jesus - Jaskelevičiūtė, Simona (Senoji Lietuvos literatūra, 2017)
-